Upaya Konservasi Tanah Berbasis Kearifan Lokal (Studi Kasus Ladang Berpindah di Desa Olilit Timur, Kecamatan Tanimbar Selatan, Kabupaten Kepulauan Tanimbar) - Maria E. J. Sarbunan; Mohammad Amin Lasaiba; Dwi Partini (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
Soil conservation is an essential effort to maintain the sustainability of natural resources, particularly in island regions vulnerable to land degradation. The shifting cultivation practice in Olilit Timur Village represents local wisdom that sustains soil fertility through land rotation and natural vegetation use. This study aims to identify and analyze the community’s role in soil conservation based on local wisdom. A descriptive qualitative method was applied, using observation, interviews, questionnaires, and documentation, involving 10 respondents. The findings reveal that shifting cultivation remains effective in maintaining land productivity, reducing erosion risks, and fostering a harmonious relationship between humans and nature. The system also reflects cultural and spiritual values that regulate land management patterns. This study concludes that such local practices can serve as a foundation for sustainable conservation strategies relevant to island communities. The implications highlight the importance of preserving local wisdom through participatory policies, and recommend integrating traditional practices with modern approaches to strengthen future food security and environmental sustainability